An Active Server Pages (ASP) Approach in Ecotourism Rating Expert System - Nair, Vikneswaran; Daud, Mohamed; Bardaie, Muhamad Zohadie; Abdullah Mohd, (Universiti Putra Malaysia Press, 2003)
The environment is the backbone of tourism products. Profitability in tourism depends on maintaining the attractiveness of the tourist destinations. Malaysia is a tropical wonderland that is substantially rich in a variety of ecological pursuits and certainly of much tourist potential. Hence, the status of the environment plays a critical role if the industry is to sustain itself. The ecotourism concept emphasises the maximisation of the ecological interest areas. This aspect, while having vast potential for further development and exploitation, has not received adequate attention in Malaysia. All ecotourism sites must be planned, guided and exploited in a monitored and controlled manner for effective and efficient management. A systematic expert rating system is developed to maintain a certain level of standards based on different levels of categorisation to ensure the sustainability of ecotourism sites in Peninsular Malaysia. The expert system developed uses a web-based information sharing platform in line with the existing legislation on safety, health and environment. The system is designed and developed on a back-end on-line database, which will keep record of all successful transactions. This paper presents an efficient model using Active Server Pages scripting method to manage and deliver the ecotourism rating expert system.